ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫНЫҢ СОЦИАЛ – ЭКОНОМИКАЛЫҚ РАЎАЖЛАНЫЎЫ (1991-1995-жж) - Есназарова, З.Б. (FAN va JAMIYAT, 2017)
The article is devoted to the analysis of the main directions of socio-economic development of the Republic of Karakalpakstan for the years of Independence. The article points to the difficulties of the initial period of Independence, and the bases of the development for the period of 1991-1995. In the historical analysis, the author of the article emphasizes that the organization of industrial enterprises in towns, the development of small business and private entrepreneurship is a requirement of the time. The article contains materials and facts in the newest-history of Karakalpakstan.